2018
DOI: 10.3389/fmicb.2018.00311
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid-Mediated Quinolone Resistance in Shigella flexneri Isolated From Macaques

Abstract: Non-human primates (NHPs) for biomedical research are commonly infected with Shigella spp. that can cause acute dysentery or chronic episodic diarrhea. These animals are often prophylactically and clinically treated with quinolone antibiotics to eradicate these possible infections. However, chromosomally- and plasmid-mediated antibiotic resistance has become an emerging concern for species in the family Enterobacteriaceae. In this study, five individual isolates of multi-drug resistant Shigella flexneri were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Dissemination and acquisition of macrolide mphA resistance mechanisms in Shigella spp. has been shown to be mainly due to spread of plasmids from E. coli 140. All the discovered mphA -associated plasmids have been identified in E. coli isolates, indicating their role as a repository from which antimicrobial resistance to Shigella spp.…”
Section: Drug-resistance Mechanisms In Shigella Sppmentioning
confidence: 99%
“…Dissemination and acquisition of macrolide mphA resistance mechanisms in Shigella spp. has been shown to be mainly due to spread of plasmids from E. coli 140. All the discovered mphA -associated plasmids have been identified in E. coli isolates, indicating their role as a repository from which antimicrobial resistance to Shigella spp.…”
Section: Drug-resistance Mechanisms In Shigella Sppmentioning
confidence: 99%
“…However, drug resistant Shigella and Campylobacter are serious threats to human and macaque health. Not only do both Shigella and Campylobacter have decreasing rates of susceptibility to fluoroquinolones (17% and 28%, respectively) and macrolides (14% and 4%, respectively), but there are reports in both humans and macaques regarding emerging fluoroquinolone-resistant Shigella strains [ 4 , 8 – 10 ]. A recent study showed that Shigella flexneri isolated from macaques contained chromosomal and plasmid-mediated fluoroquinolone resistance [ 8 ].…”
Section: Development Of Antimicrobial Resistance and Risk To Human He...mentioning
confidence: 99%
“…Class C b-Lactamase, known as AmpC-type enzymes are encoded by both chromosomal and plasmid genes. CMY-2, a plasmid encoded AmpC b-lactamase firstly identified in S. sonnei isolates which was obtained from a dysentery outbreak in Taiwan and there after CMY-2 have been reported in several countries like China, Iran, Costa Rica and India [53][54][55] . Different AmpC genes are listed in table1.…”
Section: Class C B-lactamasementioning
confidence: 99%